UJARAN KEBENCIAN DALAM UNDANG-UNDANG NOMOR 7 TAHUN 2017 TENTANG PEMILU DAN TINJAUAN SIYASAH DUSTURIYAH - Ulya Permatasari; Ulya Atsani; Muhammad Hizbi Islami (UIN Mahmud Yunus Batusangkar, 2023)
The main problem in this thesis is the regulation of hate speech in Law Number 7 of 2017, because when the agenda for a democratic party or also known as elections is approaching, the behavior of hate speech has greatly increased. Certain groups of candidates may clash with other supporting groups, so that Article 28E paragraph (3) of the 1945 Constitution of the Republic of Indonesia,